I am brave! - Greenawalt, Kelly; Rauscher, Amariah (New York : Acorn/Scholastic Inc., 2021)
In rhyming text super girl Princess Truly goes on a camping trip with little brother Ty and her dog, Sir Noodles; with her super powers she is not afraid of dark caves, bugs, or things that go bump in the night, which is a problem when she develops hiccups, and needs something to scare them away.
Ages 4-6.
Grades K-1.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Princesses -- Juvenile fiction; African American girls -- Juvenile fiction; Camping -- Juvenile fiction; Courage -- Juvenile fiction; Superheroes -- Juvenile fiction; Hiccups -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Stories in rhyme; Stories in rhyme; Princesses -- Fiction; African Americans -- Fiction; Camping -- Fiction; Courage -- Fiction; Superheroes -- Fiction; Siblings -- Fiction; Stories in rhyme; Stories in rhyme